(3GdaJM hGdHTQi aj efGbH GdRgQGs - (3GdYdhqj GdTGaYqj GdLaQj, eMeO Hf MSjf, J (B1186 (3g`s ((3jhSa Hf eMeO MeGOs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3def Lgd eMHI Bd HjJ QShd Gddg aGWeI Yf GQJVGY KOj eG dG jQVGg hfhQ djGdj hLhOge HeUHGM GdSjO GdCHQGQ aGJVMJ RgQG HYdh ebGege Ydi SGFQ GdHTQ (B...s
(3BNQgG (B:s
... (3aeQVJ ceOG Ydi CHjgG GdCYWQ , adMbJg HYO SJI CTgQ ceG gh eMbb ebQQ hcGfJ haGJgG GdKdGKGA dKdGK Ndhf ef QeVGf (B... (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\104s
(3EjVGM Gdecfhf (B2\175s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs